Complex assessment of blood pressure regulation system in hypertension patients - Natalya A. Samorodskaya; Lily V. Polischuk; Ludmila N. Eliseeva (Belgorod National Research University, 2019)
Introduction: There are almost no studies characterizing the integrative level of blood pressure (BP) regulation. Materials and methods: 277 people of both genders aged 58.6±6.4 with stage II hypertension disease were randomized into six groups. The monotherapy of hypertension disease was conducted in five groups, using nebivolol, lisinopril, indapamide, amlodipine, and losartan. The sixth group had a combined therapy (lisinopril/indapamide). The therapy effectiveness was assessed at four levels of blood pressure regulation, using the following methods: 1) laser Doppler flowmetry, determination of the level of tumor necrosis factor-α and interleukin-10; 2) echocardiography and Doppler sonography, ultrasound examination of the renal blood flow, ECG, Holter monitoring of ECG; 3) an examination of the heart rate variability level and a quantitative assessment of beta-adrenoreception of erythrocyte cell membranes; 4) the regulatory and adaptive status was assessed, using the method of cardio-respiratory synchronism. Results and discussion: A more significant BP decrease was revealed during a combination therapy (by 20.4% of the baseline daily value). At the integrative level, an index of the regulatory and adaptive status (iRAS) increased in the treatment with lisinopril/indapamide combination (by 40.5%), amlodipine (by 40.5%), losartan (by 35.3%), and lisinopril (by 30.2%). Nebivolol administration resulted in a 13.5% decrease in iRAS. Indapamide therapy had no significant effect on iRAS. Conclusion: A comprehensive assessment of the blood pressure regulation system makes it possible to control the effectiveness of the therapy not only on a target organ or function, but also on the condition of the organism as an integral system.